Analisis Keberlanjutan Pendanaan Badan Layanan Umum pada Pendapatan Petani Kopi di Desa Cinanggela, Kecamatan Pacet, Kabupaten Bandung - Jihan Syarifatullah; Faroby Falatehan; Hariyadi Hariyadi (Jurnal Ilmu Pertanian Indonesia, 2022)
Coffee is one of the most important commodities traded widely in the world. To increase coffee productivity, maintenance efforts are needed such as maintenance, land clearing, fertilization, and cultivation. All of these steps require a large amount of money. For this reason, Chinese coffee farmers need loan funds to increase their productivity and income. This study aims to determine the results of the financing provided by BLU to coffee farmers in Cinanggela Village. Data collection includes primary and secondary data. Then, the study was carried out using the Microsoft Office Excel program and the Multi-Dimensional Scaling Method through the Rapid Appraisal for Fisheries (Rapfish) software. The results obtained indicate that there is a significant increase in the income of farmers, increased by Rp12,578,381 per ha with a production yield of 7496.9 kg per ha. This means that the maintenance of coffee trees in Cinanggela Village is included in profitable farming with an R/C ratio of 2.94. Meanwhile, the results of the sustainability analysis on the economic dimension show sufficient sustainability status with an index of 56.71. The ecological dimension shows a less sustainable status with a value of 49.93. And the social dimension shows the lowest sustainability status, namely 44.09 with the attribute value of coffee sales (2.4), community participation (3.2), and the frequency of conflicts between farmers (2.6). The low values of some of these attributes need to be used as inputs to the Environmental Fund Management Agency (BPDLH) as the successor to the financing previously carried out by BLU. Keywords: coffee, sustainability funding, multi-dimensional scaling, rapfish